Final answer:
The solution to the equation x + 3 = -(x + 1) is x = -2, which is not listed among the provided options. There may be an error in the question or provided options.
Step-by-step explanation:
To find the value of x that satisfies the equation x + 3 = -(x + 1), we need to solve for x.
First, expand the right side of the equation: x + 3 = -x - 1. Then, add x to both sides of the equation to get 2x + 3 = -1. Finally, subtract 3 from both sides to obtain 2x = -4. Dividing both sides by 2 yields x = -2.
Upon examining the options provided, none of them match our solution. Therefore, there must be a mistake in the provided options or in the question as posed, because our correct solution is x = -2. This means the correct answer is not listed among the options a. x = 8, b. x = 8/3, c. x = -8/3, or d. x = -8.